Application of ZA Fertilizer on Growth and Production of Red Ginger (Zingiber officinale var. Rubrum) - Albriansyah Zinka Ancoro Putro; Supriyono Supriyono; Sulandjari Sulandjari; Djoko Purnomo (Journal of Biodiversity and Biotechnology, 2023)
Red ginger is one of the export commodities of spices in Indonesia which plays a significant role in the country's foreign exchange earnings. In order to meet market demand, ginger cultivation needs to be fertilized both organically and inorganically to increase production. ZA fertilizer for plants serves to stimulate vegetative growth. This study aims to determine the response of red ginger to the application of ZA fertilizer has a significant effect on the growth and yield of red ginger and to obtain the optimum dose of ZA fertilizer for the growth and yield of red ginger. This research was carried out in March - August 2021 until it was completed in Pelem Hamlet, Wonorejo Village, Jatiyoso District, Karanganyar Regency, Central Java Province with coordinates 7°43'24.7”S 111°05'31.2”E. The experimental design was a Completely Randomized Complete Block Design (RCBD). This study consisted of 4 treatments with 6 replications so that 24 experimental units were obtained, while the treatments in this study were as follows: P0: Control without ZA fertilizer, P1: Treatment 225 Kg ZA/ha or 22.5 g/m2, P2: Treatment 450 Kg ZA/ha or 45 g/m2, and P3: Treatment 675 Kg ZA/ha or 67.5 g/m2. The results showed that ZA fertilizer had no significant effect on the yield of red ginger, but on growth observations, P2 treatment with a dose of 450 Kg ZA/ha can have a significant effect on the increase in the number of plants per plot. The dry weight of the stover was strongly correlated with the weight of fresh rhizomes with correlation values (r) 0.508.